Effect of ammonia, darkness, and phenazine methosulfate on whole-cell nitrogenase activity and Fe protein modification in Rhodospirillum rubrum. - Kanemoto, R H (1984)
A procedure for the immunoprecipitation of Fe protein from cell extracts was developed and used to monitor the modification of Fe protein in vivo. The subunit pattern of the isolated Fe protein after sodium dodecyl sulfate-polyacrylamide gel electrophoresis was assayed by Coomassie brilliant blue protein staining and autoradiographic 32P detection of the modifying group. Whole-cell nitrogenase activity was also monitored during Fe protein modification. The addition of ammonia, darkness, oxygen, carbonyl cyanide m-chlorophenylhydrazone, and phenazine methosulfate each resulted in a loss of whole-cell nitrogenase activity and the in vivo modification of Fe protein. For ammonia and darkness, the rate of loss of nitrogenase activity was similar to that for Fe protein modification. The reillumination of a culture incubated in the dark brought about a rapid recovery of nitrogenase activity and the demodification of Fe protein. Cyclic dark-light treatments resulted in matching cycles of nitrogenase activity and Fe protein modification. Carbonyl cyanide m-chlorophenylhydrazone and phenazine methosulfate treatments caused an immediate loss of nitrogenase activity, whereas Fe protein modification occurred at a slower rate. Oxygen treatment resulted in a rapid loss of activity but only an incomplete modification of the Fe protein.